Analisis Peran Relawan UbahBareng Jabodetabek dalam Implementasi Strategi Marketing 3P untuk Pemenangan Pilpres 2024 - Wahyuni, Dewi Kamalia; Barkah, Cecep Safa’atul; Herawaty, Tetty; Auliana, Lina; Septian, Christin Dwi Putri; Sutrisno, Taufik (Jurnal Studi Ilmu Politik, 2025)
Volunteers has a crucial role in the 2024 presidential election victory of the Anies Baswedan-Muhaimin Iskandar (Anies-Imin) duo. The purpose of the study is to examine how UbahBareng Jabodetabek volunteers supported the Anies-Imin campaign by implementing the 3P political marketing strategy that is push, pull, and pass marketin). The study draws on primary and secondary data sources using qualitative approaches and a descriptive approach. According to the research findings, UbahBareng Jabodetabek uses push marketing by going to residential areas, playing fun soccer, and watching movies together. Social media branding and engaging Anies-Imin-related material are used to execute pull marketing. In the actions and initiatives that are conducted, pass marketing is carried out in cooperation with different partners. The 3P strategy implemented is effective in promoting Anies-Imin and increasing supporter involvement in order to increase the chances of Anies-Imin winning.